Colorectal cancer in a second round after a negative faecal immunochemical test. Issue 7 (July 2015) - Bujanda, Luis; Sarasqueta, Cristina; Castells, Antoni; Pellisé, María; Cubiella, Joaquín; Gil, Inés; Cosme, Angel; Arana-Arri, Eunate; Mar, Izaskun; Idigoras, Isabel; Portillo, Isabel
Abstract : Objective: The faecal immunochemical test is one of the tests recommended by scientific societies for colorectal cancer (CRC) screening in average-risk populations. Our aim was to evaluate the characteristics of CRC detected in a second round of screening after negative results in a first round. Methods: We studied patients in whom CRC was detected in a screening programme. This programme included asymptomatic individuals between 50 and 69 years old and offered tests every 2 years. A total of 363 792 individuals were invited to participate in the first round of faecal immunochemical test screening and 100 135 individuals in the second round after a first negative result. The screening strategy consisted of faecal testing of a single sample using an automated semiquantitative kit, with a cut-off of 20 μg haemoglobin (Hb)/g faeces. Results: The rate of positive results was 6.9% (16 467/238 647) in the first round and 4.8% (3359/69 193) in the second round ( P <0.0005). Overall, 860 (0.36%) cases of CRC were detected in the first round and 100 (0.14%) in the second round ( P <0.005). The location of the cancer was proximal in 12.5 and 24% of cases detected in the first and second rounds, respectively ( P =0.008). Hb concentrations were higher in the first round (211 vs. 109 μg Hb/g faeces in the second round; P =0.002). Multivariate analysis confirmed that, in the second round, CRC diagnosed was more often proximal (hazard ratio vs. first round, 2.4; 95% confidence interval, 1.3–4.4; P =0.003) and the concentration of Hb/g faeces was lower (hazard ratio vs. first round, 2.1; 95% confidence interval, 1.3–3.5; P =0.003). Conclusion: The CRC detection rate is lower in the second round of screening. Further, in the second round, CRC detected is more often in a proximal location and Hb concentrations are lower.